Determinantes da politica de dividendos: evidência empírica para as empresas não financeiras cotadas na Euronext Lisbon - Ribeiro, Alexandrino (2010)
The problematic of dividends paid out by firms has deserved the attention of several studies, theoretical and empirical, on corporate finance. This article intends to contribute to the theme by determining the factors that influence a firm’s dividends` policy. In this sense, it investigates the effect of a set of factors on the dividends paid out by issuing non financial firms belonging to Euronext Lisbon. Results suggest the existence of firm specific characteristics influencing its dividends policy. A firm’s Cash-flow and its stocks` market price seem to have a positive impact on the dividends paid out to stockholders. In issuing non financial firms that belong to the PSI 20 Index results additionally show the existence of a negative effect of net profits on dividend’s payment.